2022
DOI: 10.1002/jcu.23318
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dysfunction as the major driver of heart failure with preserved ejection fraction syndrome

Abstract: Left atrial (LA) dysfunction seems to play a central role in the pathophysiology of heart failure with preserved ejection fraction (HFpEF), is associated with disease severity and poor outcomes and potentially impacts management. Identifying LA myopathy can help guide tailored therapy for HFpEF. Echocardiography allows the accurate measurement of atrial size and function, where LA strain appears to be a sensitive measure of intrinsic LA myopathy. Several therapies and devices that decompress of left atrium are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
(177 reference statements)
0
3
0
3
Order By: Relevance
“…This study also demonstrated that left ventricular diastolic dysfunction was also associated with the hANP level, which has not been previously reported. Left atrial dysfunction and dilated left atrium were reportedly associated with HFpEF [ 14 , 15 , 23 ], thus it is plausible that increased atrial wall stress leads to a high plasma hANP level. In patients with HFpEF or systolic dysfunction, over 70% of them exhibited hANP levels ≥ 100 pg/mL, and there were no significant differences in prognosis between two groups divided by the threshold hANP level.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated that left ventricular diastolic dysfunction was also associated with the hANP level, which has not been previously reported. Left atrial dysfunction and dilated left atrium were reportedly associated with HFpEF [ 14 , 15 , 23 ], thus it is plausible that increased atrial wall stress leads to a high plasma hANP level. In patients with HFpEF or systolic dysfunction, over 70% of them exhibited hANP levels ≥ 100 pg/mL, and there were no significant differences in prognosis between two groups divided by the threshold hANP level.…”
Section: Discussionmentioning
confidence: 99%
“…Для определения для легочного венозного потока). Однако с увеличением давления в ЛП происходит смещение наполнения ЛП в следующую фазу -кондуитную [3]. Применяя метод отслеживания движения пятен (Speckle Tracking Echo, STE), можно количественно оценить деформацию резервуарной фазы левого предсердия (Left Atrial reservoir Strain, LASr), снижение которой характерно для СНсФВ [4].…”
Section: Relationships Andunclassified
“…Критерии включения: ДД со снижением ранней диастолической скорости движения фиброзного кольца митрального клапана, оцененной при помощи тканевой допплерографии (Tissue Doppler Imaging, TDI); недостаточное количество критериев для заключения о повышенном ДЗ ЛЖ по данным традиционной ЭхоКГ покоя (отсутствие 2-х либо 3-х положительных критериев из 3-х возможных). Учитывали отношение Е/е' (отношение ранней диасто- шении анализа фазовой деформации ЛП, который может получить более широкое распространение [3,4,16,17]. Неспособность миокарда ЛЖ к адекватному растяжению и прогрессирующее увеличение ДЗ ЛЖ в раннюю диастолу описывается ростом отношения E/e'; угнетение растяжения стенок ЛП в резервуарную фазу/увеличение среднего давления в ЛП выражается снижением LASr [3].…”
Section: материал и методыunclassified
“…12 Imaging methods such as echocardiography can be used to quantify the structure or function of the atria. [13][14][15][16] Left atrial reverse remodelling (LARR) reflects the degree of left atrial improvement. 17 Over the past few years, the important pathophysiological roles of left atrial expansion and dysfunction in HFpEF have become increasingly recognized, yet little is known about the association between LARR and the prognosis for patients with HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired left atrial structure and function is an important marker of increased risks of hospitalization and mortality in HFpEF patients 12 . Imaging methods such as echocardiography can be used to quantify the structure or function of the atria 13–16 . Left atrial reverse remodelling (LARR) reflects the degree of left atrial improvement 17 .…”
Section: Introductionmentioning
confidence: 99%